PENGETAHUAN REMAJA DALAM PENGGUNAAN INTERNET TENTANG INFORMASI KESEHATAN REPRODUKSI DI SMAN 4 BATAM - Netty Herawaty Purba; Indah Dwi Puspita; Sherly Mutiara; Harindra Harindra (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2022)
Knowledge will always develop because humans have the ability to think and have a high curiosity. 98% of children and adolescents know about the internet and 79.5% of them are internet users. Reproductive health problems that often occur in adolescents are unwanted pregnancies, which often lead to unsafe abortions and their complications, pregnancy and childbirth at a young age. increase the risk of maternal morbidity and mortality, STI’s including HIV/AIDS. This study's goal was to assess SMA N 4 Batam's level of familiarity with using the Internet to look up information on reproductive health. Design of research is descriptive quantitative. The sampling technique used is cluster random sampling, that is high school teenagers who have smartphones as many as 92 people. The measurement technique is by asking 25 questions about knowledge. The results of the study, it is known that most of the adolescents knowledge about reproductive health is good, namely 39 respondents (42.4%) and for internet access, which is >5 times/day with 47 respondents (51.1%). For this reason, it is still very important to educate teenagers about reproductive health to know more about reproductive health and also to use the internet better.